Cerumenolytic Efficacy of 2.5% Sodium Bicarbonate Versus Docusate Sodium: A Randomized, Controlled Trial. Issue 7 (August 2020) - Piromchai, Patorn; Laohakittikul, Chanticha; Khunnawongkrit, Sirichoke; Srirompotong, Somchai
Abstract : Objectives: To evaluate the efficacy of 2.5% sodium bicarbonate and docusate sodium in patients with complete occlusion of the ear canal from impacted cerumen. Study Design: Randomized controlled trial. Method: We enrolled patients with unilateral complete cerumen occlusion of the ear canal that was unable to be removed using suction. Either 2.5% sodium bicarbonate or docusate sodium was applied and allowed to sit for 15 minutes. The ear canal was then cleaned under a microscope for up to 3 minutes until the tympanic membrane was completely visible. A second attempt with the same agent was performed in subjects in whom the first application was unsuccessful. The outcomes were compared between the two groups in terms of cleaning, the success rate, time taken to clean the canal, and adverse events. Results: There were 91 participants enrolled in this study. The mean age of the participants was 48.0 years. The patients' demographic did not differ between the two groups. At the end of the treatment, the tympanic membrane was completely visible in 41 (91.11%) subjects treated with 2.5% sodium bicarbonate and 38 (82.61%) subjects treated with docusate sodium, with a 1.10 success ratio between the two groups (95% CI: 0.94–1.29, p  = 0.23). The mean successful suctioning time was 103.61 seconds using 2.5% sodium bicarbonate and 124.13 using docusate sodium. The mean difference was 20.52 seconds (95% CI: –10.55–51.59). Conclusion: 2.5% sodium bicarbonate demonstrated non-inferior efficacy and safety compared with docusate sodium. We recommend using this agent in clinical practice. Trial Registration: Clinicaltrials.in.th/TCTR20160803001.